Interaction of nerve agent antidotes with cholinergic systems - Soukup, O; Tobin, G; Kumar, U K; Binder, J; Proska, J; Jun, D; Fusek, J; Kuca, K (Current medicinal chemistry, 2010)
The poisoning with organophosphorus compounds represents a life threatening danger especially in the time of terroristic menace. No universal antidote has been developed yet and other therapeutic approaches not related to reactivation of acetylcholinesterase are being investigated. This review describes the main features of the cholinergic system, cholinergic receptors, cholinesterases and their inhibitors. It also focuses on the organophosphorus nerve agents, their properties, effects and a large part describes various possibilities in treatments, mainly traditional oxime therapies based on reactivation of AChE. Furthermore, non-cholinesterase coupled antidotal effects of the oximes are thoroughly discussed. These antidotal effects principally include oxime interactions with muscarinic and nicotinic receptors.
Keywords: acetylcholin; receptory cholinergní; Antidotes; cholinesterasy; chemické bojové látky; Chemical Warfare Agents; Animals; antidota; lidé; Cholinesterases; Organophosphate Poisoning; Organophosphorus Compounds; Acetylcholine; Humans; zvířata; otrava organofosfáty; Receptors, Cholinergic; organofosforové sloučeniny